The Moderating Role of Government Policy on Contractors’ Risk Attitudes in Malaysia Construction Companies - Taofeeq, D. M.; Adeleke, A. Q.; Hassan, A. K. (International Society for Everant Publisher, 2019)
Contractors’ risk attitudes influence their bidding decisions because of their exposure to uncertainties and competitions. The competing contractors may have, over time, developed different risk attitudes that are part of their own organizational culture. Different risk attitudes explain the peculiarity in how firms do their businesses. In a risky situation, individuals’ perceptions have influence on their own risk attitudes. Organizational risk attitude operates within an organization and it defines the accepted and unaccepted risks. This is attributed to how people perceived the control over the intended behavior which relies on the availability of resources, competency, educational background, support from other people and past experience in the same project. Therefore, this study aims to identify the factors affecting contractors' risk attitudes and then determine the relationship with government policy. A total of 140 copies of questionnaire were randomly distributed to the construction companies in Malaysia. Out of the 140 copies of questionnaire distributed, 124 copies were returned. Conversely, 12 copies of the questionnaire were found to be unusable due to missing data or provided the same responses to all the questions. Thus, overall, 80% of the total copies of questionnaire were usable thereby making up an effective sample of 112. Smart PLS 3 for structural equation modeling was utilized in confirming the hypotheses developed for the study. The findings of this research confirmed that government policy (rules and regulations) played a moderating role in enhancing the factors affecting contractors’ risk attitudes in construction companies in Malaysia.